The use of incorrectly posed inverse problems and catastrophe theory in acoustoplasmic studies; Resource-Efficient Technologies; No 1 - Mkrtchan (Mkrtchyan) A. R. Alpik Rafaelovich; Abrahamyan A. S.; Chilingaryan R. Yu.; Mikayelyan A. S.; Sahakyan O. G. (2019, 2019)
Title screen